2014
DOI: 10.1016/j.toxlet.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to hyperoxic lung injury and alveolar simplification in newborn rats by prenatal administration of benzo[a]pyrene

Abstract: Maternal smoking is one of the risk factors for preterm birth and for the development of bronchopulmonary dysplasia (BPD). In this study, we tested the hypothesis that prenatal exposure of rats to benzo[a]pyrene (BP), a component of cigarette smoke, will result in increased susceptibility of newborns to oxygen-mediated lung injury and alveolar simplification, and that cytochrome P450 (CYP)1A and 1B1 enzymes and oxidative stress mechanistically contribute to this phenomenon. Timed pregnant Fisher 344 rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Our results (Fig. 2A,B, E–G) showing increases in lung injury and alveolar simplification in WT (CD-1) mice following hyperoxia (85% O 2 ) was consistent with our previous studies in newborn C57BL/6J mice [29,37] and Fisher 344 rats [38] that showed similar lung phenotype after prolonged hyperoxia. Our observations showing decreased susceptibility of newborn transgenic mice carrying the human CYP1A1 -Luc promoter to lung injury and alveolar simplification supported the hypothesis that mice harboring the human CYP1A1 promoter display beneficial effects probably by modulating the endogenous expression of mouse CYP1A and phase II antioxidant enzymes such as NQO1.…”
Section: Discussionsupporting
confidence: 93%
“…Our results (Fig. 2A,B, E–G) showing increases in lung injury and alveolar simplification in WT (CD-1) mice following hyperoxia (85% O 2 ) was consistent with our previous studies in newborn C57BL/6J mice [29,37] and Fisher 344 rats [38] that showed similar lung phenotype after prolonged hyperoxia. Our observations showing decreased susceptibility of newborn transgenic mice carrying the human CYP1A1 -Luc promoter to lung injury and alveolar simplification supported the hypothesis that mice harboring the human CYP1A1 promoter display beneficial effects probably by modulating the endogenous expression of mouse CYP1A and phase II antioxidant enzymes such as NQO1.…”
Section: Discussionsupporting
confidence: 93%
“…F 2 -isoprostane, a lipid peroxidation by-product is a biomarker for oxidative stress (24,56). More recently, another marker isofuran was identified, whose concentration increases under elevated O 2 levels, making combined detection of these molecules more efficient for evaluation of hyperoxia-induced oxidative stress (60).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-established that long-term hyperoxia causes ALI characterised by oxidative stress and enhanced cell death [ 19 ]. Scarce data, however, are only available on the interaction between CS exposure and hyperoxia: pre -natal exposure to the CS component benzo[ a ]pyrene potentiated immediate post -natal hyperoxic lung injury [ 20 ], and long-term (over five days) post -natal exposure to hyperoxia had an additive effect on the histological lung damage and organ dysfunction in CS-induced COPD during adulthood [ 21 ]. However, in various animal models resulting from haemorrhage [ 22 25 ], ischemia/reperfusion injury [ 26 , 27 ] and poly-microbial sepsis [ 28 30 ] short-term ventilation with 100% O 2 resulted in attenuated inflammation and reduced apoptosis [ 26 , 27 , 29 32 ], and ultimately improved organ function and survival.…”
Section: Introductionmentioning
confidence: 99%